MPAS-Dev/MPAS-Analysis: v1.7.0 ... - Xylar Asay-Davis; Veneziani, Milena; Wolfram, Phillip J.; Van Roekel, Luke; Comeau, Darin; Brady, Riley; Stephenprice; Gstreletz; Turner, Adrian K., Kevin; Petersen, Mark; Doutriaux, Charles; et al. (Zenodo, 2022)
A minor release including 1) new density contour plots for validating eddy parameterizations; 2) E3SM-Unified testing in the test suite; 3) a smarter config parser shared with compass . This release also includes some minor clean up and bug fixes. Minor enhancement: Add flake8 to dev environment #870 Switch to MpasConfigParser for config options #873 Switch to using f90nml for reading namelists #874 Add WOCE and SOSE density contour plots #877 Add E3SM-Unified support to test suite #879 Bug fixes Reduce ncclimo tasks for Anvil to 6 #865 Update test suite to kill jobs with invalid deps #872 Add back legend for Antarctic melt flux time series #878 Clean up: Various pieces of clean up #875 Contributors @darincomeau @mark-petersen @milenaveneziani @xylar ...